Health care determinants in comparative perspective: The role of partisan politics for health care provision. (October 2013) - Montanari, Ingalill; Nelson, Kenneth
Health care differs substantially across countries in terms of service provision relevant for social citizenship. Whereas driving forces for the expansion and subsequent decline of cash benefits have received major scholarly interest in comparative research, determinants of developments in public services are less explored. In this article we assess the role of partisan politics for health care provision measured in terms of health employment, hospital beds, and medical technology. Regression analyses based on Organization for Economic Co-operation and Development Health data for 18 countries covering the period 1980–2005 show that partisan politics influences levels of health care provision. Left government strength is positively related to health care provision and the association is driven by developments in health employment. Confessional parties are also associated with high levels of health employment, particularly when they are in close electoral competition with left parties. Both left and confessional government strength is negatively associated with the provision of hospital beds, but these effects are mitigated when parties are in intense electoral competition. In terms of medical technology, we find no partisan political effects.